Phase evolution mechanism of selenium during hydrothermal conversion–atmospheric sulfuric acid leaching of copper anode slimes - Fang Shuling; Rao Shuai; Ma Zhiyuan; Liu Yejian; Tian Lei; Chen Lijie; Liu Zhiqiang; Zhang Liheng (Hydrometallurgy, 2026)

Selective recovery of vanadium, molybdenum, and nickel from full-particle spent hydrodesulfurization catalysts via microwave roasting-ammonia leaching - Haoyu Xu; Liang Yu; Zhiyuan Ma; Shuling Fang; Shuai Rao; Dongxing Wang; Lijuan Duan; Hongyang Cao; Zhiqiang Liu (Journal of Environmental Chemical Engineering, 2026)

Coupling of spectroscopy and nitrogen-oxygen isotopes unveils the mechanisms of dissolved organic matter and nitrate pollution in lakes within the agro-pastoral transition zone - Guodong Chai; Fang Yang; Haiqing Liao; Debin Jia; Weiying Feng; Chiamin Ho; Dongpin Liu; Shuling Chen; Jianguo Liu; Huibin Yu (Journal of Environmental Sciences, 2026)

Europium-labeled polystyrene tracing reveals earthworm-mediated inhibition of root uptake and reduced phytotoxicity in lettuce - Nan Chang; Shiqi Bian; Qingliang Cui; Shuling Zhao; Tianyi Qiu; Li Chen; Tao Li; Peng-yang Wang; Roland Bol; Na Wang; Zhiqin Zhang; Fengyu Huang; et al. (Journal of Hazardous Materials, 2026)

DBD synergistic UiO-66/GO-n: A new dawn for efficient defluorination and rapid degradation of fluorine-containing organic pollutants - Yejian Liu; Lijuan Duan; Shuling Fang; Wuming Xie; Qingnan Zeng; Jingyi Huang; Hongyang Cao; Zhiyuan Ma (Process Safety and Environmental Protection, 2026)

Unveiling the impacts of microplastic pollution on soil health: A comprehensive review - Nan Chang; Li Chen; Na Wang; Qingliang Cui; Tianyi Qiu; Shuling Zhao; Haoran He; Yi Zeng; Wei Dai; Chengjiao Duan; Linchuan Fang (Science of The Total Environment, 2024)

Synergistic enhancement of plant growth and cadmium stress defense by Azospirillum brasilense and plant heme: Modulating the growth–defense relationship - Qingliang Cui; Jingzi Beiyuan; Yinglong Chen; Mengdi Li; Tianyi Qiu; Shuling Zhao; Xiaozhen Zhu; Hansong Chen; Linchuan Fang (Science of The Total Environment, 2024)

Microplastic pollution promotes soil respiration: A global‐scale meta‐analysis - Shuling Zhao; Matthias C. Rillig; Haijian Bing; Qingliang Cui; Tianyi Qiu; Yongxing Cui; Josep Penuelas; Baiyan Liu; Shiqi Bian; Fazel Abdolahpur Monikh; Jing Chen; Linchuan Fang (Global Change Biology, 2024)
Microplastic (MP) pollution likely affects global soil carbon (C) dynamics, yet it remains uncertain how and to what extent MP influences soil respiration. Here, we report on a global meta‐analysis to determine the effects of MP pollution on the soil microbiome and CO 2 emission. We found that MP pollution significantly increased the contents of soil organic C (SOC) (21%) and dissolved organic C (DOC) (12%), the activity of fluorescein diacetate hydrolase (FDAse) (10%), and microbial biomass (17%), but led to a decrease in microbial diversity (3%). In particular, increases in soil C components and microbial biomass further promote CO 2 emission (25%) from soil, but with a much higher effect of MPs on these emissions than on soil C components and microbial biomass. The effect could be attributed to the opposite effects of MPs on microbial biomass vs. diversity, as soil MP accumulation recruited some functionally important bacteria and provided additional C substrates for specific heterotrophic microorganisms, while inhibiting the growth of autotrophic taxa (e.g., Chloroflexi , Cyanobacteria ). This study reveals that MP pollution can increase soil CO 2 emission by causing shifts in the soil microbiome. These results underscore the potential importance of plastic pollution for terrestrial C fluxes, and thus climate feedbacks.

A meta-analysis on crop growth and heavy metals accumulation with PGPB inoculation in contaminated soils - Xiaohan Bai; Roland Bol; Hansong Chen; Qingliang Cui; Tianyi Qiu; Shuling Zhao; Linchuan Fang (Journal of Hazardous Materials, 2024)

Meta-analysis of impacts of microplastics on plant heavy metal(loid) accumulation - Li Chen; Nan Chang; Tianyi Qiu; Na Wang; Qingliang Cui; Shuling Zhao; Fengyu Huang; Hansong Chen; Yi Zeng; Faqin Dong; Linchuan Fang (Environmental Pollution, 2024)

Interaction of microplastics with heavy metals in soil: Mechanisms, influencing factors and biological effects - Baiyan Liu; Shuling Zhao; Tianyi Qiu; Qingliang Cui; Yuyi Yang; Lili Li; Jing Chen; Min Huang; Ai Zhan; Linchuan Fang (Science of The Total Environment, 2024)

An efficient three-dimensional (3D) inversion algorithm for recovering magnetic targets when remanence exists - Yuan Fang; Shuling Li; Guofeng Liu; Xiaohong Meng; Jun Wang; Shijing Zheng (Acta Geophysica, 2024)

Slope position mediates the co-utilization of phosphorus by plants and microbes through rhizosphere processes in a phosphorus-limited forest - Tianyi Qiu; Jialuo Yu; Liyuan He; Ji Liu; Qingliang Cui; Yongxing Cui; Chengjiao Duan; Shuling Zhao; Yunqiang Wang; Linchuan Fang (CATENA, 2023)

Synergistic interplay between Azospirillum brasilense and exogenous signaling molecule H2S promotes Cd stress resistance and growth in pak choi (Brassica chinensis L.) - Qingliang Cui; Dongdong Liu; Hansong Chen; Tianyi Qiu; Shuling Zhao; Chengjiao Duan; Yongxing Cui; Xiaozhen Zhu; Herong Chao; Yuhan Wang; Jie Wang; Linchuan Fang (Journal of Hazardous Materials, 2023)

Successful application of optimized aperture based CRS stack in the Shengli exploration area - Fenggui Sui; Shuling Sui; Zhenchun Li; Xiaodong Sun; Fang Li; Dong Li (Applied Geophysics, 2009)